Computer simulation and turbine development for free flowing water generator / Mohd Ridhwan Hizami Abd Rashid - Abd Rashid, Mohd Ridhwan Hizami (2010)
Hydroelectric is an alternative way to convert mechanical energy into electricity by harnessing the flow of the rivers to run a turbine. The suitable design of river water turbine is needed to make sure that it maintains speed with flow rate at variable season during monsoon and drought. In order to complete the design of turbine system on engineering software such as CATIA and STAR CD is used. The complete design of turbine system will be attached to the turbine platform to make sure that the maximum and minimum speed can be achieved and strength of the turbine system is attained. CAE analysis will be conducted for fiirther simulation of the turbine during operation. Once the analysis and evaluation stage completed and had been approved, then it is attached to the generator. The design of the turbine can avoid environmental damage such as land erosion, jungle flooding and lots of flora and fauna. No damp or weir is used in order to rotate the turbine. By finishing this thesis, the author hopes that the turbine can be further develop for commercial used in the future and a self-sustainable community can be achieved, without fully depends on the oil-based power generation. The system will be tested at Kuala Keniam River, UiTM-Pehilitan Research Station and investigated the water turbine performance and efficiency. If everything works as planned, progress of fabrication until installation process will proceeds smoothly and successful.